Superior Efficacy of Midostaurin Over Cladribine in Advanced Systemic Mastocytosis: A Registry-Based Analysis. Issue 16 (1st June 2022) - Lübke, Johannes; Schwaab, Juliana; Naumann, Nicole; Horny, Hans-Peter; Weiß, Christel; Metzgeroth, Georgia; Kreil, Sebastian; Cross, Nicholas C.P.; Sotlar, Karl; Fabarius, Alice; Hofmann, Wolf-Karsten; Valent, Peter; et al.
Abstract : PURPOSE: On the basis of data from the German Registry on Disorders of Eosinophils and Mast Cells, we compared the efficacy of midostaurin and cladribine in patients with advanced systemic mastocytosis (AdvSM). PATIENTS AND METHODS: Patients with AdvSM (n = 139) were treated with midostaurin only (n = 63, 45%), cladribine only (n = 23, 17%), or sequentially (midostaurin-cladribine, n = 30, 57%; cladribine-midostaurin, n = 23, 43%). Prognosis was assessed through the Mutation-Adjusted Risk Score (MARS). Besides the comparison of efficacy between midostaurin and cladribine on response (eg, organ dysfunction, bone marrow mast cell [MC] infiltration, and tryptase), overall survival (OS), and leukemia-free survival, we focused on the impact of treatment on involved non-MC lineages, for example, monocytes or eosinophils, and the KIT D816V expressed allele burden. RESULTS: Midostaurin only was superior to cladribine only with effects from responses on MC and non-MC lineages conferring on a significantly improved OS (median 4.2 v 1.9 years, P = .033) and leukemia-free survival (2.7 v 1.3 years, P = .044) on the basis of a propensity score–weighted analysis of parameters included in MARS. Midostaurin compensated the inferior efficacy of cladribine in first- and second-line treatment. On midostaurin in any line, response of eosinophilia did not improve its baseline adverse prognostic impact, whereas response of monocytosis proved to be a positive on-treatment parameter. Multivariable analysis allowed to establish three risk categories (low/intermediate/high) through the combination of MARS and the reduction of the KIT D816V expressed allele burden of ≥ 25% at month 6 (median OS not reached v 3.0 years v 1.0 year; P < .001). CONCLUSION: In this registry-based analysis, midostaurin revealed superior efficacy over cladribine in patients with AdvSM. In midostaurin-treated patients, the combination of baseline MARS and molecular response provided a compelling three-tier risk categorization (MARSv2.0) for OS. Abstract :